The Influence of Macroeconomic Factors and Bank Health Ratios on Non-Performing Loan (A Case Study: Bank Rakyat Indonesia) - Kurnia Firmansyah, M Rizky Indra; `Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research seeks to examine the factors that influence the NPL level BRI, considering the NPL trend BRI has improved relatively compared to other KBMI IV Banks and has a large focus on lending to the UMKM sector which inherently has higher credit risk. The variables used in this research are inflation, GDP, CAR, LDR, NIM, & BOPO to the NPL level BRI uses a quantitative approach with models Error Correction Model (ECM). The research results show that in the short term inflation, LDR, and NIM has a significant effect on NPL, while GDP, CAR, and BOPO have no significant effect. However, in the long term inflation, CAR and NIM have a significant effect on NPL, while GDP, LDR, and BOPO are not significant. Thus, the implication of this research is that banks can focus on managing credit risk and debtors can understand the factors that can influence their ability to pay, thereby supporting better decision making for both parties.